INTERTEKSTUAL DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY DAN NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL KHALIEQY - Saputri, Desi; Martono, Martono; Priyadi, Antonius Totok (Universitas Tanjungpura, 2023)
This study aims to describe the intertextuality in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy and the novel Perempuan Berkalung Turban by Abidah El Khalieqy through its intrinsic elements and how it is implemented in learning Indonesian at school. The research method used is descriptive with a qualitative research form. The data sources in this study were two novels which were the object of research and the data were intertextual from the novel Bidadari Bermata Bening and the novel Perempuan Berkalung Turban. The results of the research show that there is an intertextuality of the two novels based on the intrinsic elements of the two novels such as the themes of family muruah, forced marriage, struggle, and happiness. Characters and characterizations such as Ayna and Anisa, Yoyok and Samsudin, Gus Afif and Lek Khudori, Neneng and Nina. The plot is backwards, and the setting is the foyer of the mosque, the time setting is morning, evening and night. The background atmosphere is a sad, emotional, happy, and angry atmosphere. This research can be implemented in the 2013 curriculum for senior high school grade XI even semester with KD 3.20. Analyzing messages from two fiction books (novels and poetry collections) read